Work Engagement Terhadap Komitmen Kerja Buruh - M. Choirul Ibad; Linda Mora; Ai Teti (Jurnal Multidisiplin Ibrahimy, 2023)
The purpose of this research is to analyze the effect of Work Engagement on organizational commitment. This study uses a quantitative approach method. The population used in this study were employees of PT. Daesang Food Indonesia. Scale were distributed offline and data were analyzed using a simple regression test using SPSS 25. The number of respondents used in the study were 94 employees. The results of the study prove that there is a 10.1% effect of Work Engagement on organizational commitment at PT. Daesang Food Indonesia.